A case study of a community-organized wastewater surveillance in a small community: correlating weekly reported COVID-19 cases with SARS-CoV-2 RNA concentrations during fall 2020 to summer 2021 in Yarmouth, ME. (27th February 2023) - Brooks, Yolanda M.; Gryskwicz, Bailey; Sidaway, Eilidh; Shelley, Brianna; Coroi, Laura; Downing, Margaret; Downing, Tom; McDonnell, Sharon; Ostrye, Dan; Hoop, Katrina; Parrish, Gib
Abstract: Wastewater surveillance offers a rapid evaluation of SARS-CoV-2 transmission in a community. We describe how a community group, the Yarmouth Wastewater Testing Team (YWTT), in Yarmouth, Maine, (population 8, 990) utilized an asset-based community design framework to organize and manage a program to monitor SARS-CoV-2 RNA concentrations. From September 22, 2020 through June 8, 2021, the YWTT disseminated weekly reports of the wastewater results and reported COVID-19 cases within the Yarmouth postal code. After high and increasing SARS-CoV-2 RNA concentrations, the YWTT issued two community advisories to encourage extra care to reduce exposure. Correlations between SARS-CoV-2 RNA concentrations and COVID-19 cases were stronger the week after sampling, and the average of the COVID-19 cases during the week of sampling and the following week, indicating that surveillance provided advance notice of cases. A 10% increase in SARS-CoV-2 RNA concentrations was associated with a 13.29% increase in the average number of weekly reported cases of COVID-19 during the week of sampling and the following week (R2 = 0.42; p < 0.001). Adjusting for viral recovery (December 21, 2020 through June 8, 2021), improved R2 from 0.60 to 0.68. Wastewater surveillance was an effective tool for the YWTT to quickly respond to viral transmission. HIGHLIGHTS: Community organizations can successfully design wastewater surveillance programs. Weekly wastewater surveillance correlates to weekly reported COVID-19 cases. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA concentrations are best correlated to cases the same week and the following week. Adjusting for viral recovery increased the fit of linear regression by 8%. Community-based initiatives can effectively respond to an increased viral transmission. Graphical Abstract